Diets based on soybean protein for Mediterranean fruit fly - Sobrinho, Raimundo Braga; Caceres, Carlos; Islam, Amirul; Wornoayporn, Vivat; Enkerlin, Walter (Pesquisa Agropecuaria Brasileira, 2006)
The objective of this work was to develop suitable and economic diets for mass rearing Mediterranean fruit fly, Ceratitis capitata (Diptera: Tephritidae). Diets containing sugar beet bagase, wheat bran, brewer yeast, and others with wheat bran and palletized soybean protein from Brazil were tested. Diets based on soybean protein have shown promising results regarding pupal recovery, pupal weight and adult emergence. Soybean bagase in the form of pellets with 60% of protein can be a very important substitute for other expensive sources of protein.